Trends in Environmental Education and Science Research: A Four-Decade Bibliometric Review - Husamah; Norizhati; Cahyono, Shafa Rimbi Riskia; Rahardjanto, Abdulkadir; Permana, Tutut Indria; Lestari, Nurdiyah; Adlini, Miza Nina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study employs bibliometric analysis to explore research trends over the past four decades, focusing on publications indexed in the Scopus database. The data were processed using bibliometric analysis tools such as VOSviewer and Biblioshiny (RStudio). Guided by ten key research questions, the study examines publication growth, leading authors, institutions, funding bodies, and patterns of international collaboration. It also analyzes subject areas, highly cited articles, prominent sources, keyword trends, and generates bibliometric visualizations such as word clouds.The findings reveal a significant increase in publication volume, with rapid growth observed after 2009 and a peak between 2013 and 2018, reflecting growing global awareness and interdisciplinary efforts. Dominant fields include environmental science, education, and sustainability, with highly cited works providing foundational contributions to the field. Institutions such as Colorado State University and funding agencies like the National Science Foundation emerge as key contributors, emphasizing the importance of collaboration and research funding. Evolving research priorities highlight the use of innovative methods such as virtual reality and data visualization to enhance environmental literacy. Bibliometric visualizations reveal key research clusters centered on interdisciplinary learning, sustainability education, and advanced methodologies. However, challenges remain in aligning global and regional priorities and translating research findings into practice. Future efforts should focus on integrating diverse perspectives, fostering global collaboration, and leveraging emerging technologies to drive innovation. Strengthening the connection between environmental science and education is essential for tackling global issues and advancing sustainable development.